Physical, Chemical and Rheological Characterization of Tuber and Starch from Ceiba aesculifolia subsp. parvifolia - Lizette Suastegui-Baylón; Ricardo Salazar; Yanik I. Maldonado-Astudillo; Manuel O. Ramírez-Sucre; Gerónimo Arámbula-Villa; Verónica Flores-Casamayor; Javier Jiménez-Hernández (Molecules, 2021)
This work aimed to evaluate the physical, chemical and antioxidant properties of Ceiba aesculifolia subsp. parvifolia (CAP) tuber and determinate rheological, thermal, physicochemical and morphological properties of the starch extracted. The CAP tuber weight was 3.66 kg; the edible yield was 82.20%. The tuber presented a high hardness value (249 N). The content of carbohydrates (68.27%), crude fiber (15.61%) and ash (9.27%) from the isolated starch, reported in dry weight, were high. Phenolic compounds and flavonoid content of CAP tuber peel were almost 3-fold higher concerning the pulp. CAP tuber starch exhibited a pseudoplastic behavior and low viscosity at concentrations of 5–15%. Purity percentage and color parameters describe the isolated starch as high purity. Thermal characteristics indicated a higher degree of intermolecular association within the granule. Pasting properties describes starch with greater resistance to heat and shear. CAP tuber starch has X-ray diffraction patterns type A. The starch granules were observed as oval and diameters ranging from 5 to 30 µm. CAP tuber could be a good source of fiber and minerals, while its peel could be used for extracting bioactive compounds. Additionally, the starch separated from this tuber could be employed as a thickening agent in food systems requiring a low viscosity and subjected to high temperatures.